(untitled) (Journal of Global Accounting, 2023)
The study examined the effect of adoption of Treasury Single Account on accountability and transparency in tertiary institutions in Nigeria. The study equally determined the extent to which the adoption of Treasury Single Account helps to control fraud and fraudulent practices in tertiary institutions in Anambra state. The research design adopted for this study is the survey design. The population of this study comprised 490 Bursary staffs of three (3) selected tertiary institutions in Anambra State which included Nnamdi Azikiwe University Awka, Federal Polytechnic Oko and Federal College of Education Technical Umunze. A survey instrument was administered on a sample of 220 respondents obtained using Taro Yamane formula for sample size determination. To analyze the primary data collected, descriptive statistics and inferential statistics were employed with the aid of Statistical Package for Social Science (SPSS) software (Version 22). Spearman Ranked Order Correlational Analysis was applied in testing the hypotheses of the study. The study found the following: Treasury Single Account adoption has a significant positive influence on the accountability of public funds in Tertiary Institutions in Anambra State (rho = 0.558, p-value = 0.000); Treasury Single Account adoption has significantly improved transparency in public fund management in tertiary institutions in Anambra State (rho = 0.433, p-value = 0.000); Treasury Single Account has a significant role in controlling fraud and fraudulent practices in tertiary institutions in Anambra State (rho = 0.191, p-value = 0.006). In conclusion, the TSA system contributes to a more responsible and efficient utilization of public funds by enabling better fund management, providing greater visibility, and establishing stringent controls. It was recommended that public institutions should conscientiously implement and effectively utilise the TSA system to maintain transparency and strengthen financial oversight